Avoidable Pitfalls: Another Encounter of Bilateral Ureter Complete Duplication with Impacted Calculus At Al Habib Hospital/Dubai - Fahmi Mohamed Abu Shawish; Georgios Kapsas (Dr. Sulaiman Al Habib Medical Journal)
The ureter is commonly the subject of congenital anatomical variations involving either complete or incomplete duplication. Complete ureter duplication may not produce symptoms and therefore does not become apparent until later in life. This condition is most encountered incidentally during the extraction of impacted ureteric stones. This type of anomaly is more common in females. However, this condition is not the extremely rare incident as previously thought. Herein, we present our second case of bilateral complete ureter duplication. This aberration was encountered during the extraction of an impacted calculus which was found close to the vesico-ureteric junction of the medial limb of the right complete duplicated ureter. We also present a review of the related English literature. It is essential to emphasize the importance of our basic knowledge relating to most possible renal and ureteric surgical aberrations. A particular consideration prior to any procedure is the meticulous analysis of related radiological images. This clinical practice is a key priority if we are to avoid unpleasant surgical pitfalls. The in-depth diagnosis of an aberration basically remains a radiological entity. This case study provides learning points to complement our daily practice in the management of impacted ureteric calculi.